Identification of Biology Education Research during The Covid-19 Pandemic - Maesaroh Maesaroh (STAI Hubbulwathan Duri, 2022)
The Covid-19 pandemic has had an impact on various educational activities. Routine activities carried out were forced to switch digitally using internet facilities, including student research activities. Quality research affects the improvement of the quality of education.This study aims to determine the characteristics of biology education carried out by final year students during the Covid-19 pandemic. The survey method was used in the research with the instrument in the form of a questionnaire sheet with semi-open questions. The results showed that biology education research carried out during the pandemic mostly used descriptive and quasi-experimental methods. There are meta-analytical research methods from international journals with PRISMA guidelines and literature studies with scoping review techniques that are relatively new by students. A total of 71.9% of the study used a sample of students at the high school and college level. As many as 76% of research data were obtained online, 19% of research activities were blended, and only about 5% of students obtained research data offline. Constraints experienced by students during research are: 1) Internet network is not stable, 2) students are difficult to be asked to turn on the camera in the data collection process, 3) it is relatively difficult to collect respondent responses in online questionnaires, 4) constrained by research time due to the large number of school holidays, 5) online communication becomes an obstacle in conducting research guidance.